Understanding the extension capacity needs of the CapeNature Stewardship Programme in the Western Cape Province of South Africa - Coetzee, Johannes Christiaan (Rhodes University, Faculty of Science, Department of Environmental Science, 2018)
There is an increasing call for conservation programmes to provide sound evidence of effectiveness, and employing empirical evaluations can assist in the transition to evidence-based conservation practices. The objectives of this research were to develop a logic model for the CapeNature Stewardship Programme which would articulate the programme's theory of operation with respect to its Stewardship Programme landholders. The second major objective was to develop psychometric instruments for assessing the motivations and satisfactions of the programme's stewardship landholders. Both objectives included the aim to provide robust and repeatable instruments for exploring landholder's psychology, and developing a programme's theory of operation to understand the programme and improve with understanding the needs of the landowners. In this regard the processes and methodologies employed represent a major component of this research. A mixed methods approach was utilized, including stakeholder and volunteer surveys, conducted via mailing hardcopies and the internet, together with three focus groups held with the programme's management, extension staff and the stewardship landholders. Analysis of the data thus collected included both qualitative and quantitative approaches, specifically coding and content analysis, together with statistical tests of internal consistency, factor analysis and doubling correspondence analysis. Robust indices for example validity and internal consistency were developed for assessing landholder's satisfaction with extension and level of satisfaction with the stewardship programme (Babbie 2007). These indices revealed that landholders in the Stewardship Programme are not satisfied with the programme, and exhibit behaviours suggesting they act as advocates for the programme. Demographic data and additional information provided further insights into the programme. The development of a method for articulating the programme's theory of operation is represented, together with four logic models which graphically illustrate this theory. This process and theory allowed for recommendations to be provided for the programme's improvement. A platform for adaptive management and further evaluations of this, and similar programmes, represents a major outcome of this research, understanding the extension capacity needs for the conservation of biodiversity in the CapeNature Stewardship Programme to function as a model for improving the implementation of the programme across the Western Cape, South Africa. This research feeds into an evaluation of CapeNature's Biodiveristy Stewardship programme and demonstrates the importance of incorporating psychology into conservation interventions.
Keywords: Conservation projects (Natural resources); Psychometrics; Adaptive natural resource management; Biodiversity conservation; CapeNature Stewardship Programme